Style in architecture: the combination of diverse elements in Cheong Fatt Tze mansion in Penang / Nur’Ain Athirah Amran and Izzat Anuar - Amran, Nur’Ain Athirah; Anuar, Izzat (2023)
The Cheong Fatt Tze Mansion or so-called Blue Mansion is a prominent landmark in Penang and an example to embrace the beauty of the Straits eclectic style. However, the future architectural development in Penang does not share the same concern on maintaining and preserving the values because of their lack of understanding. The paper investigates the elements, characteristics of the architectural style and the architectural layout of a mansion in George Town, Penang, as well as the architectural style of the mansion. The structure of Cheong Fatt Tze Mansion combines Chinese architectural and cultural ideas with local Malay ethnicity and European colonial influences. This research is produced by using systematic data which is primary data and secondary data. The primary data will be collected through a site visit, recording the data from personal interviews with the expert and owner of the mansion. The secondary data will be gathered using diverse online sources, such as official publications, non-governmental organization (NGO) websites, and archived news. The findings of this research point toward a better understanding of the Straits Eclectic style and the elements in the Cheong Fatt Tze itself. Lastly, this gem needs to be preserved in other to portray the Late Straits Eclectic style for future reference.